The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1001/jama.2015.12334
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a Buffered Crystalloid Solution vs Saline on Acute Kidney Injury Among Patients in the Intensive Care Unit

Abstract: clinicaltrials.gov Identifier: ACTRN12613001370796.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
439
4
16

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 613 publications
(467 citation statements)
references
References 17 publications
(30 reference statements)
8
439
4
16
Order By: Relevance
“…There are also indications that balanced solutions are associated with advantages in terms of patient survival [32]. But in contrast, a recently published study found no survival benefit of balanced solution compared to saline solution [33]; however, the applied amount of infusion was so small in this study (<2 l applied slowly during the course of several days) that neither the chloride concentration nor the pH in the saline group could increase above or drop below the respective normal values. At ISICEM 2016, Kellum presented results from a very large cohort of patients demonstrating that larger amounts of saline solution were associated with increased mortality compared to balanced solutions.…”
Section: Crystalloidscontrasting
confidence: 75%
“…There are also indications that balanced solutions are associated with advantages in terms of patient survival [32]. But in contrast, a recently published study found no survival benefit of balanced solution compared to saline solution [33]; however, the applied amount of infusion was so small in this study (<2 l applied slowly during the course of several days) that neither the chloride concentration nor the pH in the saline group could increase above or drop below the respective normal values. At ISICEM 2016, Kellum presented results from a very large cohort of patients demonstrating that larger amounts of saline solution were associated with increased mortality compared to balanced solutions.…”
Section: Crystalloidscontrasting
confidence: 75%
“…Normal saline, still one of the most employed intravenous crystalloid solutions, presents a non-physiologically high, content of Cl -(and Na + ), and has long been known to induce hyperchloremic metabolic acidosis. Despite the fact that some studies (mainly uncontrolled or retrospective) have shown that unbalanced solutions may not be as innocent as previously thought [3−5], only recently, the SPLIT trial has shed some new light on this issue [6]. This trial (the 0.9% Saline vs. Plasma-Lyte 148 for Intensive Care Unit Fluid Therapy) is the first large randomized controlled trial comparing the clinical effects of two different types of crystalloids [6].…”
Section: Balanced Versus Unbalanced Solutionsmentioning
confidence: 99%
“…Despite the fact that some studies (mainly uncontrolled or retrospective) have shown that unbalanced solutions may not be as innocent as previously thought [3−5], only recently, the SPLIT trial has shed some new light on this issue [6]. This trial (the 0.9% Saline vs. Plasma-Lyte 148 for Intensive Care Unit Fluid Therapy) is the first large randomized controlled trial comparing the clinical effects of two different types of crystalloids [6]. In this double-blind, cluster randomized, double-crossover trial, conducted in 4 ICUs in New Zealand, 2,278 ICU patients in need of crystalloid fluid therapy were enrolled to receive either 0.9% NaCl or Plasma-Lyte 148, as a balanced solution, according to an alternating block of 7-weeks for each specific ICU.…”
Section: Balanced Versus Unbalanced Solutionsmentioning
confidence: 99%
See 2 more Smart Citations